High-intensity interval training improves mitochondrial function and attenuates cardiomyocytes damage in ischemia-reperfusion - Zhan Wei; Mujahid Ahmad; Rongzhi Chen; Sana Fatima; Shahab Shah (International Journal of Cardiology: Heart & Vasculature, 2025)
Ischemic heart disease remains a leading cause of global mortality and morbidity, underscoring the urgent need for effective therapies particularly for patients recovering from ischemic cardiac events. High-intensity interval training (HIIT) has emerged as a promising non-pharmacological intervention with substantial cardioprotective potential. Both clinical studies and animal models demonstrate that HIIT attenuates cardiac damage induced by ischemia–reperfusion injury. However, the precise cellular and molecular mechanisms underlying these benefits remain incompletely elucidated. Mitochondria play a pivotal yet dual role in ischemia–reperfusion injury, serving as central regulators of both cell survival and death pathways. Although HIIT is recognized to modulate mitochondrial function, its specific impact on cardiac susceptibility to ischemic injury requires further clarification. This review synthesizes current evidence on the beneficial effects of HIIT on cardiac mitochondrial function, with a focus on the mechanisms through which it confers cardioprotection. We examine how HIIT may enhance mitochondrial resilience by activating critical signaling pathways that mitigate ischemia–reperfusion injury. Despite significant advances, key knowledge gaps persist. This review emphasizes the necessity of further research to fully unravel HIIT’s cardioprotective potential and its role in promoting mitochondrial adaptation under ischemic stress.